APLIKASI BAHAN PELAPIS BENIH DAN LAMA PENYIMPANAN TERHADAP VIABILITAS BENIH DAN PERTUMBUHAN TOMAT CERI (Solanum lycopersicum var cerasiforme) - Bella, Wahyu Okta; Anwar, Syaiful; Karno, Karno (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Cherry tomatoes have high economic value, but their production is low, this is due to the low quality of seeds. Coating and storage are efforts made to maintain seed quality. This study aims to examine the effect of coating materials and shelf life on seed viability and cherry tomato growth. The experimental design used is Time Series with a long storage series and coating on seeds. The long storage consists of 4 levels; 0, 30, 60, and 90 days and the Coating Material consists of 4 levels; uncoating, PEG 6000, Arabic Gum, Galangal Powder, and Clove Oil with 3 replications. The data analyzed with Honest Real Difference Test. The results showed that Clove oil hasn’t effect the germination. Uncoated and unstored seeds have the highest moisture content. Plant height, number of leaves, fresh weight of the stamp, dry weight of the stamp, and flowering time have no effect, this is due to internal factors such as seed genetics and external factors such as the concentration of coating materials and plant growth environment.